Mineral wool melt, mineral wool and preparation method

By adjusting the composition and smelting process of mineral wool melt, the problem of complex and high cost of converting non-ferrous smelting tailslag into rock mineral wool fibers in the prior art is solved, and the mineral wool melt with high forming performance and heat resistance is achieved, simplifying the process flow and improving metal recovery efficiency.

CN115849722BActive Publication Date: 2025-03-28HUNAN RE TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202211453376.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-21
Publication Date
2025-03-28
Estimated Expiration
2042-11-21

AI Technical Summary

Technical Problem

When the prior art uses nonferrous smelting tailings to produce rock mineral wool fibers, the process is complex, the cost is high, and it is difficult to effectively recover metals such as low contents of iron, copper, and lead.

Method used

By adjusting the composition of the mineral wool melt, including 40-43 wt% SiO2, 10-12 wt% Al2O3, 19-21 wt% CaO, 7-9 wt% MgO, etc., the acidity coefficient Mk is 1.8-2.0, and a specific smelting process and tempering agent combination is used to prepare a mineral wool melt with excellent forming performance.

Benefits of technology

The high forming performance, heat resistance and chemical stability of mineral wool melts are achieved, which reduces smelting costs, simplifies the process flow, and can effectively recover valuable metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003952479320000071
    Figure BDA0003952479320000071
  • Figure BDA0003952479320000081
    Figure BDA0003952479320000081
  • Figure BDA0003952479320000131
    Figure BDA0003952479320000131
Patent Text Reader

Abstract

The present invention relates to a mineral wool melt, mineral wool and a preparation method. The mineral wool melt comprises the following components: 40-43wt% SiO2, 10-12wt% Al2O3, 19-21wt% CaO, 7-9wt% MgO, 0-3wt% B2O3, 0-5wt% Na2O, 0-5wt% K2O and 10-15wt% total iron converted to Fe2O3; wherein the total content of Na2O and K2O is ≤5wt%; and the acidity coefficient Mk of the mineral wool melt is 1.85-1.95. The mineral wool melt of the present invention has suitable components and excellent forming performance. The cotton fiber produced has high fire resistance and strong chemical stability, and has high fiber forming rate and low slag ball content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a mineral wool melt, mineral wool and a preparation method, and belongs to the technical field of thermal insulation materials. Background Art

[0002] A large amount of slag is inevitably produced during the non-ferrous metal smelting process. It is the main solid waste of non-ferrous metal smelting enterprises and a bulk industrial solid waste that urgently needs to be disposed of.

[0003] The slag from nonferrous metal smelting such as lead and copper is mainly CaO-FeO-SiO2 slag type. The tailings are currently generally converted into glassy water-quenched slag by water quenching, and the residual heavy metals are sealed in the glass body, and then used in building aggregates, cement additives and other building materials or landfill treatment, and the value of resource utilization is low. The tailings include SiO2, Fe2O3, CaO, Al2O3, MgO and a small amount of residual metals, etc. The composition is similar to that of rock wool in mineral wool, and can replace natural raw materials such as basalt in rock wool production.

[0004] Chinese invention patent CN 102161567 B discloses a method for producing mineral wool fibers by utilizing the sensible heat of molten waste slag from smelting nickel alloy in an electric furnace. The molten waste slag from smelting nickel alloy in an electric furnace is mixed and melted with limestone, dolomite and basalt powder in proportion, with an acidity coefficient of 1.3 to 1.5, and then formed into mineral wool fibers by a four-roll centrifuge.

[0005] Chinese invention patent CN 103952564 B discloses a method for treating copper smelting slag, wherein the copper smelting slag is mixed with a slag-making agent and a reducing agent, and copper and iron are obtained respectively through two smelting processes, and finally the smelting slag is made into silk to obtain inorganic fibers.

[0006] Chinese invention patent application CN 104975123 A discloses a method for preparing copper-containing cast iron and slag wool from molten copper slag, wherein molten copper slag and a reducing agent are added into an electric furnace for smelting to obtain copper and iron, and the molten tailings are discharged from a slag outlet and poured into a slag holding furnace for homogenization treatment to obtain slag wool.

[0007] Chinese invention patent application CN 106746690 A discloses a method for preparing mineral fiber from secondary slag of copper slag, wherein the secondary slag treated with copper slag is evenly mixed with calcium-containing waste slag such as quicklime and carbide slag and silicon-containing waste slag such as fly ash, river sand, and waste glass, finely ground, and then melted and kept warm to obtain molten liquid slag, which is then cooled in an intermediate tank to produce mineral fiber.

[0008] Although there are many methods to apply non-ferrous smelting tailings to the production of rock wool fibers, the technical maturity is not high enough, and the existing technology is mostly to first smelt to remove iron and recover copper, lead and other metals. The process review shows that it is difficult to smelt and recover low-content iron, copper and lead from the tailings, which is not conducive to reducing the smelting cost. Secondly, the composition of non-ferrous smelting tailings is quite different from that of basalt and diabase, and low-content valuable metals remain. The composition system and smelting process of rock wool melt in the existing technology cannot adapt well to non-ferrous smelting tailings, and the cost of industrial production is high. Summary of the invention

[0009] In view of the deficiencies in the prior art, one of the objects of the present invention is to provide a mineral wool melt with excellent forming properties; a second object of the present invention is to provide a method for preparing the mineral wool melt; a third object of the present invention is to provide a mineral wool.

[0010] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0011] A mineral wool melt comprises the following components: 40-43wt% SiO2, 10-12wt% Al2O3, 19-21wt% CaO, 7-9wt% MgO, 0-3wt% B2O3, 0-5wt% Na2O, 0-5wt% K2O and 10-15wt% total iron converted to Fe2O3; wherein the total content of Na2O and K2O is ≤5wt%; and the acidity coefficient Mk of the mineral wool melt is 1.8-2.0.

[0012] Furthermore, the mineral wool melt comprises the following components: 40-42wt% SiO2, 10.5-11.5wt% Al2O3, 19.5-20.5wt% CaO, 7.5-8.5wt% MgO, 1.5-2.5wt% B2O3, 0-4wt% Na2O, 0-4wt% K2O and 12-14wt% total iron converted to Fe2O3; wherein the total content of Na2O and K2O is ≤4wt%; and the acidity coefficient Mk of the mineral wool melt is 1.85-1.95.

[0013] In the present invention, the acidity coefficient M k It is the ratio of the total mass of SiO2 and Al2O3 in the mineral wool melt to the total mass of CaO and MgO, that is: M k =(SiO2+Al2O3) / (CaO+MgO).

[0014] Furthermore, in the total iron, the proportion of FeO (ie the ratio of the mass of FeO to the mass of total iron) is ≥80wt%; further ≥85wt%.

[0015] Furthermore, the mineral wool melt may also include: MnO and / or Cr2O3, wherein the content of MnO is less than 5wt%, the content of Cr2O3 is less than 3wt%, and the total content of MnO and Cr2O3 is less than 5wt%. Preferably, in the mineral wool melt, the total content of MnO, Cr2O3 and total iron is 10-15wt%.

[0016] Furthermore, the melting temperature of the mineral wool melt is 1450-1550° C. In the present invention, the melting temperature refers to the temperature corresponding to when the melt viscosity of the mineral wool melt is ≤0.1 Pa·s.

[0017] Furthermore, the upper limit temperature of crystallization of the mineral wool melt is 1200-1350°C.

[0018] Furthermore, the temperature drop corresponding to the change of the viscosity of the mineral wool melt from 0.5Pa·s to 5Pa·s is 100-150°C, the temperature drop corresponding to the change of the viscosity of the mineral wool melt from 5Pa·s to 20Pa·s is 60-100°C, and the temperature drop corresponding to the change of the viscosity of the mineral wool melt from 20Pa·s to 50Pa·s is 40-70°C.

[0019] Furthermore, the temperature drop corresponding to the change of the viscosity of the mineral wool melt from 0.5Pa·s to 5Pa·s is 110-140°C, the temperature drop corresponding to the change of the viscosity of the mineral wool melt from 5Pa·s to 20Pa·s is 70-90°C, and the temperature drop corresponding to the change of the viscosity of the mineral wool melt from 20Pa·s to 50Pa·s is 50-70°C.

[0020] Based on the same inventive concept, the present invention also provides a method for preparing the mineral wool melt as described above, comprising the following steps:

[0021] S1. Taking non-ferrous smelting tailings and determining the composition of the non-ferrous smelting tailings;

[0022] According to the composition of the above non-ferrous smelting tailings, the type of conditioning agent is selected and the composition of the conditioning agent is determined;

[0023] Wherein, the conditioning agent includes one or more of SiO2 conditioning agent, Al2O3 conditioning agent, CaO conditioning agent, MgO conditioning agent, and B2O3 conditioning agent;

[0024] S2. Calculate the ratio of non-ferrous smelting tailings and conditioning agent according to the composition of the mineral wool melt to obtain the formula of the mineral wool melt;

[0025] S3. According to the formula of the mineral wool melt, non-ferrous smelting tailings and a conditioning agent are weighed and mixed evenly to obtain a batch material, which is then put into a slag furnace for melting and homogenization to obtain a mineral wool melt.

[0026] Furthermore, the slag type of the non-ferrous smelting tailings is CaO-FeO-SiO2. Furthermore, the non-ferrous smelting tailings include one or more of lead slag, copper slag and nickel slag.

[0027] Generally, the tailings from nonferrous smelting such as lead and copper are mainly of the CaO-FeO-SiO2 type. The components of the tailings include SiO2, Fe2O3, CaO, Al2O3, MgO and a small amount of residual metals. The components are similar to the rock wool in mineral wool and can be used to replace natural raw materials such as basalt in the production of rock wool.

[0028] Optionally, the non-ferrous smelting tailings include one or more of manganese slag and chromium slag.

[0029] Optionally, the non-ferrous smelting tailings are one or more of the fuming furnace tailings from lead concentrate smelting, the tailings from oxygen-enriched side-blowing smelting of copper-containing sludge, the tailings from copper concentrate depletion furnace smelting, the lime-neutralized slag tailings from the hot sulfuric acid leaching bottom liquor of pyrolusite electrolysis process, the tailings from oxygen-enriched top-blowing smelting of nickel concentrate, and the chromium slag discharged from chromium salt chemical industry.

[0030] Furthermore, in S1, the non-ferrous smelting tailings is a dried water-quenched slag sample, or a glass or sintered sample that is dried and then melted at a high temperature of 1500±50°C, and the mass lost during the high-temperature melting process is recorded as the loss on ignition, and the sum of its composition and the loss on ignition is 100wt%; further, for non-ferrous metal smelting furnaces in production, the tailings composition can be determined by regular sampling, and the frequency of measurement shall not be less than once per furnace.

[0031] Furthermore, the SiO2 conditioning agent is one or more of quartz, silica, and quartz-rich tailings; the Al2O3 conditioning agent is one or more of coal gangue, fly ash, kaolin, secondary aluminum ash, and waste glass; the CaO conditioning agent is one or more of lime, limestone, wollastonite, and garbage fly ash; the MgO conditioning agent is one or more of talc, magnesite, dolomite, and forsterite; the B2O3 conditioning agent is one or more of borax, boric acid, colemanite, and forsterite.

[0032] Furthermore, the SiO2 conditioning agent may contain Al2O3, and the total content of SiO2 and Al2O3 is greater than 80wt%; the Al2O3 conditioning agent may contain SiO2, and the total content of SiO2 and Al2O3 is greater than 80wt%, the total content of Na2O and K2O is less than 12wt%, and the content of other impurities is less than 5wt%; the CaO conditioning agent may contain SiO2 and Al2O3, and the total content of Na2O and K2O is less than 2wt%; the MgO conditioning agent may contain SiO2 and Al2O3, and the total content of Na2O and K2O is less than 2wt%.

[0033] Preferably, the conditioning agent is a raw material containing two or more components of SiO2, Al2O3, CaO, and MgO, so as to reduce the types of conditioning agents.

[0034] Optionally, the tempering agent is composed of SiO2 tempering agent, Al2O3 tempering agent, CaO tempering agent, and MgO tempering agent, the SiO2 tempering agent is quartz, the Al2O3 tempering agent is coal gangue and treated secondary aluminum ash, the CaO tempering agent is wollastonite, and the MgO tempering agent is forsterite.

[0035] Optionally, the conditioning agent is composed of SiO2 conditioning agent, Al2O3 conditioning agent, CaO conditioning agent, and MgO conditioning agent, the SiO2 conditioning agent is quartz-rich tailings, the Al2O3 conditioning agent is coal gangue and treated secondary aluminum ash, the CaO conditioning agent is limestone, and the MgO conditioning agent is talc.

[0036] Optionally, the tempering agent consists of Al2O3 tempering agent, CaO tempering agent, and MgO tempering agent, the Al2O3 tempering agent is coal gangue and waste glass, the CaO tempering agent is limestone, and the MgO tempering agent is dolomite and forsterite.

[0037] Optionally, the conditioning agent is composed of Al2O3 conditioning agent, CaO conditioning agent, and MgO conditioning agent, the Al2O3 conditioning agent is fly ash and waste glass, the CaO conditioning agent is limestone, and the MgO conditioning agent is dolomite and forsterite.

[0038] Optionally, the conditioning agent is composed of SiO2 conditioning agent, Al2O3 conditioning agent, CaO conditioning agent, MgO conditioning agent, and B2O3 conditioning agent, the SiO2 conditioning agent is quartz, the Al2O3 conditioning agent is fly ash, the CaO conditioning agent is garbage fly ash, the MgO conditioning agent is talc, and the B2O3 conditioning agent is colemanite.

[0039] Optionally, the conditioning agent is composed of SiO2 conditioning agent, Al2O3 conditioning agent, CaO conditioning agent, and B2O3 conditioning agent, the SiO2 conditioning agent is quartz, the Al2O3 conditioning agent is coal gangue, the CaO conditioning agent is wollastonite, and the B2O3 conditioning agent is colemanite and magnesia stone.

[0040] Furthermore, in S3, a reducing agent is added to the slag furnace, and the amount of the reducing agent added is 0.08 to 0.16 times the total content of iron in the batch. Furthermore, the reducing agent is one or more of waste activated carbon, coke, and coal.

[0041] Furthermore, during the melting process of S3, the smelting atmosphere can be controlled to enrich part of the metal remaining in the tailings by volatilization or formation of ferroalloys, and the remaining part is wrapped by the glassy mineral wool melt and finally fixed in the cotton fibers. The toxic leaching can meet the limit values ​​in the "Hazardous Waste Identification Standard Leaching Toxicity Identification" (GB 5085.3-2007).

[0042] Furthermore, in S3, when the non-ferrous smelting tailings is cold slag, it is first mixed evenly with a tempering agent to form a batch material, and then put into the slag furnace; when the non-ferrous smelting tailings is a liquid melt, it can be directly introduced into the slag furnace.

[0043] Furthermore, the particle size of the conditioning agent is in the range of 0.045 to 30 mm, and the water content is less than 1 wt %. Preferably, the particle size is in the range of 0.045 to 0.150 mm.

[0044] Optionally, for mixing different types of conditioning agents, when the particle size of the conditioning agent is greater than 0.150 mm, mechanical mixing is used; when the particle size of the conditioning agent is less than 0.150 mm, pneumatic mixing or mechanical mixing is used. Preferably, when the particle size of the conditioning agent is less than 0.150 mm, pneumatic mixing is used.

[0045] Furthermore, in S3, waste cotton, slag balls, etc. generated in the production of mineral wool are added to the slag furnace, and the amount of addition is less than 10wt% of the tempering agent; further, the waste cotton, slag balls, etc. must be ground and dried before being added.

[0046] Furthermore, in S3, the slag furnace is a double melting pool structure, including a smelting pool and a clarification pool, the smelting pool and the clarification pool are separated by a partition wall, and a connecting port for connecting the smelting pool and the clarification pool is provided on the partition wall; the smelting pool is provided with a feeding port, a flue and a first molten iron discharge port, and the bottom of the smelting pool is provided with an inflation port; the clarification pool is provided with a discharge port and a second molten iron discharge port.

[0047] Furthermore, in S3, the liquid non-ferrous smelting tailings melt in the smelting furnace is directly drained to the smelting pool of the smelting furnace through a chute.

[0048] Optionally, the non-ferrous smelting tailings melt is water-quenched or air-cooled and ground into powder before being added into the slag furnace.

[0049] Preferably, the liquid non-ferrous smelting tailings melt in the smelting furnace is directly drained to the smelting pool of the slag furnace through the chute to reduce production energy consumption. Furthermore, when the liquid non-ferrous smelting tailings melt in the smelting furnace is directly drained to the slag furnace through the chute, the flow rate is measured; further, the flow rate is measured in an online real-time manner.

[0050] Furthermore, when the liquid non-ferrous smelting tailings melt in the smelting furnace is directly drained to the slag furnace through the chute, the amount used is a calculated value, that is, the product of the flow rate and the density.

[0051] Furthermore, in S3, the melting temperature is 1450-1550°C, and the melting time is 60-120 minutes. Furthermore, during the melting process, one or more of fuel gas, oxygen, and inert gas are blown into the bottom of the slag furnace, so that the target gas can be introduced and a strong stirring effect can be played to promote material mixing.

[0052] Furthermore, in S3, during homogenization, the melt temperature is controlled to be 1400-1500° C., the melt viscosity is not greater than 0.5 Pa·s, and the homogenization time is not less than 6 hours.

[0053] Furthermore, the various components described in the present invention are all components measured after the material is burned at 1500° C. for 30 minutes to form a sinter or glass body. Furthermore, the sum of the measured components and the loss on burning is 100%.

[0054] Based on the same inventive concept, the present invention also provides a mineral wool, which is prepared from the mineral wool melt as described above or prepared from the mineral wool melt prepared by the preparation method as described above.

[0055] Alternatively, the mineral wool melt is subjected to multi-roll centrifugal or blow molding to obtain cotton-like artificial inorganic fibers.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] (1) The mineral wool melt of the present invention has suitable composition and excellent forming performance. The cotton fiber produced has a higher operating temperature, stronger chemical stability and lower thermal conductivity, and has a high fiber formation rate and a low slag ball content.

[0058] (2) The present invention can apply non-ferrous metal smelting tailings to the production of rock wool, and coordinately dispose of various solid wastes or hazardous wastes such as coal gangue, fly ash, garbage fly ash, secondary aluminum ash, etc., to achieve waste treatment.

[0059] (3) Compared with conventional rock wool melt, the mineral wool melt of the present invention has a higher Fe2O3 content and a lower Al2O3 content, which is suitable for the composition characteristics of non-ferrous metal smelting tailings with high iron and low aluminum, can reduce the smelting and iron removal process in the prior art, and reduce the melting energy consumption.

[0060] (4) The mineral wool melt of the present invention has a high iron content, and the iron is mainly in the form of divalent iron, so that it has a suitable temperature-viscosity gradient, which can improve the forming ability of the melt and the heat resistance of the cotton fiber.

[0061] (5) The present invention can smelt nonferrous metal smelting tailings in one step to obtain a mineral wool melt, and recover part of the valuable metals remaining in the tailings during the smelting process, so that the process flow is more streamlined and the smelting efficiency is improved.

[0062] (6) The mineral wool melt and melting process provided by the present invention can directly utilize liquid tailings melt and integrate it with metal smelting, and can also utilize water-quenched or air-cooled tailings, and has good adaptability. DETAILED DESCRIPTION

[0063] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0064] The material components used in each embodiment and comparative example are shown in Table 1.

[0065] Table 1 Material composition used in each embodiment and comparative example

[0066]

[0067]

[0068] Note: In Table 1:

[0069] Lead slag A, metals are 0.94wt% Zn, 0.07wt% Pb, 0.10wt% Cu;

[0070] Lead slag B, metal is 1.76wt% Zn, 0.47wt% Pb;

[0071] Copper slag A, metal is 0.23wt% Cu;

[0072] Copper slag B, metal is 0.27wt% Cu, 0.38wt% Sn;

[0073] Nickel slag, metal is 1.81wt% Ni, 0.69wt% Cu;

[0074] Manganese slag, metal is 0.21wt% Zn, 0.13wt% Pb;

[0075] Chromium slag, metal is 0.25wt% Ti.

[0076] Example 1

[0077] A mineral wool melt is obtained by melting analytically pure reagents in a nitrogen atmosphere, and includes the following components: SiO2, Al2O3, Fe2O3, FeO, CaO, MgO, B2O3, Na2O, K2O, and an acidity coefficient M k=1.89, wherein the total amount of iron calculated as Fe2O3 is 13.78wt%, and the proportion of FeO is 92.34%. The specific components of the melt are shown in Table 3, and the thermal properties of the melt are shown in Table 4.

[0078] Example 2

[0079] Repeat Example 1, the only difference is the acidity coefficient M k =1.84. The specific composition of the melt is shown in Table 3, and the thermal properties of the melt are shown in Table 4.

[0080] Example 3

[0081] Repeat Example 1, the only difference is the acidity coefficient M k =1.95. The specific composition of the melt is shown in Table 3, and the thermal properties of the melt are shown in Table 4.

[0082] Example 4

[0083] Example 1 was repeated, except that the melt included the following components: SiO2, Al2O3, Fe2O3, FeO, CaO, MgO, B2O3, Na2O, K2O, MnO, Cr2O3, and the acidity coefficient M k =1.89, of which the total iron content calculated as Fe2O3 is 13.78wt%, and FeO accounts for 92.39%; the total content of MnO and Cr2O3 is 4.2wt%, and the total content of the total iron content calculated as Fe2O3 and the total content of MnO and Cr2O3 is 13.78%. The specific components of the melt are shown in Table 3, and the thermal properties of the melt are shown in Table 4.

[0084] Example 5

[0085] Example 1 was repeated, except that the proportion of FeO was 80.10%. The specific components of the melt are shown in Table 3, and the thermal properties of the melt are shown in Table 4.

[0086] Example 6

[0087] A mineral wool melt is prepared by smelting the lead slag A in Table 1, wollastonite powder, coal gangue powder, secondary aluminum ash, quartz powder and forsterite powder, as follows:

[0088] The measured compositions of lead slag A and various conditioning agents are shown in Table 1.

[0089] According to the components of lead slag A and various conditioning agents, the formula containing lead slag A and conditioning agents is calculated, as shown in Table 2. In terms of dry weight parts, the formula includes: 30 parts of lead slag A, 34 parts of wollastonite powder, 20 parts of coal gangue powder, 6 parts of treated secondary aluminum ash, 5 parts of quartz powder, and 13 parts of forsterite powder. The total iron content in the batch calculated as Fe2O3 is 15.88wt% (i.e., the iron content is 11.11wt%). Among them, lead slag A is water-quenched slag powder, and lead slag A, wollastonite powder, coal gangue powder, secondary aluminum ash, quartz powder and forsterite powder are all dry powders with a particle size of ≤0.074mm.

[0090] According to the formula, lead slag A and various conditioning agents are selected, and the reducing agent is waste activated carbon powder, and the amount is 0.12 times the iron content, that is, 1.33wt% (1.5 parts), and then a pneumatic mixing tank is used to mix evenly to obtain a batch containing lead slag A and conditioning agents, and then put into a slag furnace, and smelt at a temperature of 1500±25℃ for 60min to obtain a melt. During this period, nitrogen is blown from the bottom of the smelting furnace. The total amount of feed is 100kg / h, and the flow rate is 0.1Nm 3 / h. After the smelting is completed, the air blowing is stopped and the heat preservation is continued for 6 hours to homogenize and form a stable mineral wool melt, which is then discharged from the discharge port of the slag furnace and fiberized by compressed air blowing to obtain cotton fibers. The composition of the mineral wool melt extracted from the discharge port is shown in Table 3, the thermal properties are shown in Table 4; the properties of the fibers are shown in Table 5.

[0091] Example 7

[0092] A mineral wool melt is prepared by smelting the copper slag B in Table 1, nickel slag powder, tailings powder, coal gangue powder, secondary aluminum ash, limestone powder and talcum powder, as follows:

[0093] The measured compositions of copper slag B, nickel slag powder and various conditioning agents are shown in Table 1.

[0094] According to the composition of copper slag B, nickel slag powder and various conditioning agents, the formula containing copper slag B, nickel slag and conditioning agents is calculated, as shown in Table 2. In terms of dry weight, the formula includes: 30 parts of copper slag B, 15 parts of nickel slag powder, 10 parts of tailings powder, 12 parts of coal gangue powder, 4.5 parts of treated secondary aluminum ash, 25 parts of limestone powder, and 18 parts of talcum powder. The total iron content in the batch calculated as Fe2O3 is 15.83wt% (i.e., the iron content is 11.07wt%). Among them, copper slag B is hot tailings, nickel slag powder is water-quenched slag powder, tailings powder is gold tailings powder, and nickel slag powder, tailings powder, coal gangue powder, secondary aluminum ash, limestone powder and talcum powder are all dry powders with a particle size of ≤0.074mm.

[0095] According to the formula, nickel slag powder and various conditioning agent ingredients are selected, and the reducing agent is waste activated carbon powder, and the amount is 0.16 times the iron content, that is, 1.77wt% (2.0 parts) and 6 parts (5.24%) of waste cotton and slag balls that are dried and crushed to a particle size of ≤0.074mm are mixed evenly in a pneumatic mixing tank to obtain a conditioning agent batch containing nickel slag powder. The liquid melt of copper slag B is drained from the slag outlet of the oxygen-enriched side-blowing furnace through a "U" chute to the smelting pool of the slag furnace, and the flow rate is continuously measured. The conditioning agent batch is added at the same time according to the ratio of 30 parts of copper slag B and 84.5 parts of conditioning agent batch, wherein copper slag B is the melt weight calculated according to the flow rate and melt density, and the conditioning agent batch is the conditioning agent batch after deducting the added waste activated carbon powder, waste cotton and slag balls.

[0096] Copper slag B and tempering agent batch materials are smelted in the smelting pool of the slag furnace at 1500±25℃ for 80±10min to obtain a melt. During this period, a mixed gas of oxygen and nitrogen with an oxygen concentration of 60vol% is blown from the bottom of the smelting pool. The total amount of feed is 6t / h, and the flow rate is 8.5Nm 3 / h (excluding gas for heating). The melt flows into the clarifier from the opening separating the smelting pool and the clarifier, stays in the clarifier for 8 to 12 hours, is homogenized to form a stable mineral wool melt, is discharged from the discharge port of the slag furnace clarifier, and is fiberized by a four-roller centrifuge to obtain cotton fiber. The waste cotton and slag balls produced are collected, dried, and crushed into powder with a particle size of ≤0.074mm, and mixed with the tempering agent batch; the nickel- and copper-containing molten iron produced in the smelting pool is cooled and collected for the recovery of nickel, copper and iron. The composition of the mineral wool melt extracted from the discharge port is shown in Table 3, and the thermal properties are shown in Table 4; the properties of the fiber are shown in Table 5.

[0097] Example 8

[0098] A mineral wool melt is smelted by smelting the manganese slag, fly ash, waste glass powder, limestone powder, dolomite powder and forsterite powder in Table 1. The smelting process is basically the same as that of Example 6, except that: the measured components of the manganese slag and the conditioning agents are shown in Table 1; the formula of the manganese slag and the conditioning agents is shown in Table 2, the total iron content in the batch calculated as Fe2O3 is 11.92wt% (i.e., the iron content is 8.34wt%); the reducing agent added is coal powder, and the amount used is 0.08 times the iron content, i.e., 0.67wt% (0.9 parts); the mineral wool melt extracted from the discharge port has the composition shown in Table 3 and the thermal properties shown in Table 4; the properties of the fiber are shown in Table 5.

[0099] Example 9

[0100] A mineral wool melt is smelted from copper slag A, coal gangue, waste glass, limestone, dolomite and forsterite in Table 1. The smelting process is basically the same as that of Example 6, except that: the measured components of copper slag A and various conditioning agents are shown in Table 1; the formula of copper slag A and conditioning agents is shown in Table 2, wherein copper slag A, coal gangue, waste glass, limestone, dolomite and forsterite are all sandy raw materials with a particle size of 0 to 5 mm, and the total iron content in the batch calculated as Fe2O3 is 15.01wt% (i.e., the iron content is 10.50wt%); the reducing agent added is granular coal, and the amount used is 0.14 times the iron content, i.e., 1.47wt% (1.8 parts); the mineral wool melt extracted from the discharge port has the composition shown in Table 3, and the thermal properties are shown in Table 4; the properties of the fiber are shown in Table 5.

[0101] Example 10

[0102] A mineral wool melt is smelted from lead slag A, quartz powder, fly ash, garbage fly ash, talcum powder and calcite powder in Table 1. The smelting process is basically the same as that of Example 6, except that: the measured components of lead slag A and various conditioning agents are shown in Table 1; the formula of lead slag A and conditioning agents is shown in Table 2, the total iron content in the batch is 12.51wt% (i.e., the iron content is 8.75wt%) in terms of Fe2O3; the reducing agent is coke powder, and the amount used is 0.11 times the iron content, i.e., 0.96wt% (1.1 parts); the melt is fiberized by a two-roll centrifugal method to obtain cotton fibers. The mineral wool melt extracted from the discharge port has the following components, see Table 3, and the thermal properties are shown in Table 4; the properties of the fibers are shown in Table 5.

[0103] Embodiment 11

[0104] A mineral wool melt is smelted from manganese slag, chromium slag, quartz, coal gangue, wollastonite, colemanite and boraxite in Table 1. The smelting process is basically the same as that of Example 10, except that: the measured components of manganese slag, chromium slag and tempering agents are shown in Table 1; the formulas of manganese slag, chromium slag and tempering agents are shown in Table 2, the total iron content in the batch calculated as Fe2O3 is 11.62wt% (i.e., the iron content is 8.13wt%); the amount of reducing agent used is 0.10 times the iron content, i.e., 0.81wt% (0.9 parts); the mineral wool melt extracted from the discharge port has the components shown in Table 3 and the thermal properties shown in Table 4; the properties of the fiber are shown in Table 5.

[0105] Comparative Example 1

[0106] Repeat Example 1, except that the acidity coefficient M k =1.75. The specific composition of the melt is shown in Table 3, and the thermal properties of the melt are shown in Table 4.

[0107] Comparative Example 2

[0108] Repeat Example 1, except that the acidity coefficient M k =2.06. The specific composition of the melt is shown in Table 3, and the thermal properties of the melt are shown in Table 4.

[0109] Comparative Example 3

[0110] Example 1 was repeated, except that the proportion of FeO was 64.19%. The specific components of the melt are shown in Table 3, and the thermal properties of the melt are shown in Table 4.

[0111] Comparative Example 4

[0112] Example 1 was repeated, except that the total amount of iron in the mineral wool melt, calculated as Fe2O3, was 8.99 wt%. In this comparative example, in order to control the other components within the composition range of the present invention, the total content of Na2O and K2O was adjusted. The specific composition of the melt is shown in Table 3, and the thermal properties of the melt are shown in Table 4.

[0113] Comparative Example 5

[0114] Example 1 was repeated, except that the total amount of iron in the mineral wool melt, calculated as Fe2O3, was 16.78 wt%. The specific composition of the melt is shown in Table 3, and the thermal properties of the melt are shown in Table 4.

[0115] Comparative Example 6

[0116] Example 4 was repeated, with the only difference being the total content of MnO and Cr2O3. The specific composition of the melt is shown in Table 3, and the thermal properties of the melt are shown in Table 4.

[0117] Comparative Example 7

[0118] Example 4 was repeated, with the only difference being the content of Cr2O3. The specific components of the melt are shown in Table 3, and the thermal properties of the melt are shown in Table 4.

[0119] Comparative Example 8

[0120] Example 4 was repeated, except that the content of B2O3 was changed. In this comparative example, the total content of Na2O and K2O was adjusted to keep the contents of other components consistent with those of Example 4. The specific components of the melt are shown in Table 3, and the thermal properties of the melt are shown in Table 4.

[0121] Comparative Example 9

[0122] Example 10 was repeated except that no reducing agent was used.

[0123] Comparative Example 10

[0124] Example 10 was repeated, except that the amount of reducing agent used was 0.06 times the iron content, i.e., 0.53 wt % (0.61 parts).

[0125] Comparative Example 11

[0126] Example 10 was repeated, except that the amount of reducing agent used was 0.20 times the iron content, i.e., 1.75 wt % (2.01 parts).

[0127] Table 2 Raw material formula of mineral wool melt of Examples 6 to 11 and Comparative Examples 9 to 11 (unit: part)

[0128]

[0129]

[0130] Table 3 Composition of mineral wool melts in various embodiments and comparative examples

[0131]

[0132]

[0133] Note: R2O in the table refers to the total content of Na2O and K2O.

[0134] Table 4 Performance index table of mineral wool melts in various embodiments and comparative examples

[0135]

[0136] The thermal properties of mineral wool melt are the key factors affecting mineral wool production. Specifically, the melting temperature determines the energy consumption, and the temperature-viscosity gradient and the upper limit temperature of crystallization affect the forming process. Viscosity is the dominant parameter for evaluating the thermal properties of the melt. Due to the difficulty in measuring viscosity, its forming properties are usually characterized by the temperature drop at a fixed viscosity difference, that is, the temperature-viscosity gradient. Within the viscosity range of fiber forming, the greater the temperature difference, the more conducive it is to obtain slender fibers. If the temperature difference is too small, the melt will harden before it has time to form fibers, which is not conducive to the forming process. The upper limit temperature of crystallization characterizes the trend and difficulty of crystallization of mineral wool melt, and is an important reason for the formation of slag balls. The higher the upper limit temperature of crystallization, the easier it is for the melt to crystallize during the cooling process, making the fibers brittle and even forming slag balls. Composition is the basis for determining the thermal properties of mineral wool melt. At present, mineral wool generally adopts the acidity coefficient [M k =(SiO2+A2O3) / (CaO+MgO)] is an important indicator for evaluating cotton fiber quality, and the increase of acidity coefficient is beneficial to improving the forming properties of mineral wool melt, but the composition of mineral wool melt is complex, and its thermal properties cannot be well characterized by relying solely on acidity coefficient.

[0137] After extensive research, the present invention has discovered a mineral wool melt with excellent performance. It can be seen from the data in Tables 3 and 4 that with the increase of the acidity coefficient, the melting temperature of the mineral wool melt increases, the upper limit temperature of crystallization decreases, and the temperature-viscosity gradient decreases. When the acidity coefficient is controlled within the range of 1.8 to 2.0, it has a suitable melting temperature, upper limit temperature of crystallization and temperature-viscosity gradient. The iron content and valence state have a great influence on the melt performance. Under the condition of constant iron content, increasing the proportion of FeO is beneficial to improving the thermal properties of the melt. The introduction of MnO and / or Cr2O3 will cause the thermal properties of the melt to deteriorate, but controlling the introduction amount can still obtain a melt with excellent thermal properties, and the introduction of B2O3 can improve the thermal properties of the melt, especially balancing the effects of MnO and Cr2O3.

[0138] Table 5 Fiber properties of Examples 6 to 11 and Comparative Examples 9 to 11

[0139]

[0140]

[0141] The cotton fiber performance parameters in this table are in accordance with the Test Methods for Mineral Wool and Its Products (GBT 5480-2017).

[0142] It can be seen from the data in Tables 3 and 5 that cotton fibers with excellent heat resistance can be obtained by using smelting slags and industrial solid wastes such as lead slag, copper slag, nickel slag, manganese slag, and chromium slag, and by melting the ingredients according to the mineral wool melt of the present invention. The comparison of the amount of reducing agent shows that the content and valence of iron have a significant effect on the slag ball content produced in the forming process and the heat resistance of the cotton fibers. Although the introduction of MnO and / or Cr2O3 will cause the thermal properties of the melt to deteriorate, cotton fibers with excellent performance can still be obtained, especially the heat resistance of the fibers can be significantly improved; while the introduction of B2O3 will cause the temperature resistance of the fibers to decrease, so the amount of B2O3 introduced must be controlled.

[0143] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

Claims

1. A mineral wool melt, characterized in that: The mineral wool melt comprises the following components: 40-43 wt% SiO2, 10-12 wt% Al2O3, 19-21 wt% CaO, 7-9 wt% MgO, 0.01-3 wt% B2O3, 0-5 wt% Na2O, 0-5 wt% K2O and 10.87%-15 wt% total iron converted to Fe2O3; wherein the total content of Na2O and K2O is ≤5 wt%; the acidity coefficient Mk of the mineral wool melt is 1.8-2.0; In the total iron, the proportion of FeO is ≥80 wt%.

2. The mineral wool melt according to claim 1, characterized in that Also includes: MnO and / or Cr2O3, wherein the content of MnO is less than 5 wt%, the content of Cr2O3 is less than 3 wt%, and the total content of MnO and Cr2O3 is less than 5 wt%.

3. The mineral wool melt according to claim 2, characterized in that The total content of MnO, Cr2O3 and total iron is 10~15wt%.

4. The mineral wool melt according to claim 1, characterized in that The melting temperature of the mineral wool melt is 1450-1550°C.

5. The mineral wool melt according to claim 1, characterized in that The upper limit temperature of crystallization of the mineral wool melt is 1200-1350°C.

6. The mineral wool melt according to claim 1, characterized in that The temperature drop corresponding to the change of the viscosity of the mineral wool melt from 0.5 Pa·s to 5 Pa·s is 100~150℃, the temperature drop corresponding to the change of the viscosity of the mineral wool melt from 5 Pa·s to 20 Pa·s is 60~100℃, and the temperature drop corresponding to the change of the viscosity of the mineral wool melt from 20 Pa·s to 50 Pa·s is 40~70℃.

7. A method for preparing a mineral wool melt according to any one of claims 1 to 6, characterized in that: The steps include: S1. Taking non-ferrous smelting tailings and determining the composition of the non-ferrous smelting tailings; According to the composition of the non-ferrous smelting tailings, the type of tempering agent is selected and the composition of the tempering agent is determined; wherein the tempering agent includes one or more of SiO2 tempering agent, Al2O3 tempering agent, CaO tempering agent, MgO tempering agent and B2O3 tempering agent; S2. Calculate the ratio of non-ferrous smelting tailings and conditioning agent according to the composition of the mineral wool melt to obtain the formula of the mineral wool melt; S3. According to the formula of the mineral wool melt, non-ferrous smelting tailings and a conditioning agent are weighed and mixed evenly to obtain a batch material, which is then put into a slag furnace for melting and homogenization to obtain a mineral wool melt.

8. The preparation method according to claim 7, characterized in that: The slag type of the non-ferrous smelting tailings is CaO-FeO-SiO2.

9. The preparation method according to claim 7, characterized in that: The SiO2 conditioning agent is one or more of quartz, silica, and quartz-rich tailings; the Al2O3 conditioning agent is one or more of coal gangue, fly ash, kaolin, secondary aluminum ash, and waste glass; the CaO conditioning agent is one or more of lime, limestone, wollastonite, and garbage fly ash; the MgO conditioning agent is one or more of talc, magnesite, dolomite, and forsterite; the B2O3 conditioning agent is one or more of borax, boric acid, colemanite, and forsterite.

10. A mineral wool, characterized in that: The invention is prepared from the mineral wool melt according to any one of claims 1 to 6 or prepared from the mineral wool melt prepared by the preparation method according to any one of claims 7 to 8.

Citation Information

Patent Citations

  • Method for smelting nickel alloy by utilizing ore-smelting electric furnace and producing mineral wool fiber by melting waste residues and utilizing sensible heat

    CN102161567B

  • Copper smelting slag treatment method

    CN103952564B

  • Method for preparing copper-containing cast iron and slag cotton from molten copper slag

    CN104975123A

  • Method for preparing mineral fiber by using secondary copper slag

    CN106746690A

  • Raw material for producing basalt fibres

    CN103429543A